Filter‐dispersal assembly of lowland Neotropical rainforests across the Andes. Issue 11 (12th March 2018) - Bemmels, Jordan B.; Wright, S. Joseph; Garwood, Nancy C.; Queenborough, Simon A.; Valencia, Renato; Dick, Christopher W.
Abstract : Numerous Neotropical rainforest species are distributed in both Amazonia and Central America, reflecting a rich history of biotic interchange between regions. However, some plant lineages are endemic to one region, due in part to the dispersal barrier posed by the Northern Andean Cordilleras and adjacent savannas. To investigate the role of biogeographic filtering across the northern Andes in regional community assembly, we examined environmental tolerances, functional traits, and biogeographic distributions of >1000 woody plant species (trees, shrubs, lianas) locally co‐occurring in forest plots in lowland Panama (542 species) and Amazonian Ecuador (667 species). High regional abundance was strongly predictive of the probability of being geographically widespread (i.e. present on both sides of the Andes). However, we also found that species with broad environmental tolerances (those that are able to inhabit high elevations and areas of low mean annual precipitation) were more likely to have a cross‐Andean distribution even after accounting for regional abundance, suggesting that biogeographic filtering for these traits has mediated cross‐Andean dispersal. Regional abundance and environmental tolerances were additionally associated with a suite of life‐history traits related to high dispersal–colonization ability, but most traits reflecting dispersal–colonization ability were not predictive of biogeographic distribution. Our results highlight how the process of biogeographic filtering, based primarily on environmental tolerances, has mediated regional‐scale floristic assembly of Neotropical rainforests. The impacts of this process, which we term filter‐dispersal assembly, are likely to be especially important to forests in Central America, where biotic interchange with Amazonia has heavily influenced regional community composition.